Real‐world outcome of crizotinib for anaplastic lymphoma kinase‐positive lung cancer: Multicenter retrospective analysis in South Korea - Da Som Jeon; Cheol‐kyu Park; Seung Joon Kim; Chan Kwon Park; Yoon Soo Chang; Chi Young Jung; Sung Yong Lee; Shin‐Yup Lee; Jeong‐Seon Ryu; Jeong Eun Lee; Kye Young Lee; Tae Won Jang; et al. (Thoracic Cancer, 2024)
Abstract Background About 3%–5% of non‐small cell lung cancer (NSCLC) presents positive anaplastic lymphoma kinase (ALK). Recently, several target agents have been approved as a treatment for ALK‐positive NSCLC. This study aimed to analyze the real‐world efficacy and outcome when administered crizotinib, the first approved target agent for ALK‐positive NSCLC, according to first‐ or late‐line treatment. Methods A total of 290 patients with ALK‐positive advanced NSCLC who were treated with crizotinib in 15 institutions in South Korea from January 2009 to December 2018 were enrolled. Results The median age of patients was 57.0 years, and 50.3% were male. The median follow‐up duration was 29.3 months. Among them, 113 patients received crizotinib as first‐line therapy. The objective response rate (ORR) was 60.1% (57.0% for first‐line recipients, 61.8% for second−/later‐line). Median (95% CI) progression‐free survival (PFS) was 13.7 (11.6–17.0) months. For first‐line recipients, overall survival (OS) was 26.3 (17.6–35.0) months. No significant difference in ORR, PFS and OS, according to the setting of crizotinib initiation, was observed. In a multivariate Cox regression analysis, old age, male gender, initially metastatic, and number of metastatic organs were associated with poor PFS and OS. The most common adverse events were nausea and vomiting, and severe adverse event leading to dose adjustment was hepatotoxicity. Conclusions ORR, PFS, OS, and adverse event profiles were comparable to previous clinical trials. Our findings could aid in the efficient management of ALK‐positive lung cancer patients.